Autophagy, innate immunity, and cardiac disease - Santovito, Donato; Steffens, Sabine; Barachini, Serena; Madonna, Rosalinda (Frontiers in Cell and Developmental Biology, 2023)
Autophagy is an evolutionarily conserved mechanism of cell adaptation to metabolic and environmental stress. It mediates the disposal of protein aggregates and dysfunctional organelles, although non-conventional features have recently emerged to broadly extend the pathophysiological relevance of autophagy. In baseline conditions, basal autophagy critically regulates cardiac homeostasis to preserve structural and functional integrity and protect against cell damage and genomic instability occurring with aging. Moreover, autophagy is stimulated by multiple cardiac injuries and contributes to mechanisms of response and remodeling following ischemia, pressure overload, and metabolic stress. Besides cardiac cells, autophagy orchestrates the maturation of neutrophils and other immune cells, influencing their function. In this review, we will discuss the evidence supporting the role of autophagy in cardiac homeostasis, aging, and cardioimmunological response to cardiac injury. Finally, we highlight possible translational perspectives of modulating autophagy for therapeutic purposes to improve the care of patients with acute and chronic cardiac disease.